Screening of Reference Genes for Quantitative Real-time PCR in Curcuma alismatifolia Bracts - Jianjun TAN; Lishan HUANG; Yiwei ZHOU; Yechun XU; Yuanjun YE (Guangdong nongye kexue)
【Objective】To screen suitable reference genes for Quantitative Real-time PCR(qRT-PCR) analysis in Curcuma alismatifolia bract, establishing the theoretical foundation for investigating the functional genes associated with bract color.【Method】Nine C. alismatifolia cultivars with different colors were employed in this experiment. Based on the genomic information of C. alismatifolia, eight housekeeping genes including glyceraldehyde-3-phosphate dehydrogenase (GAPDH), 18S rRNA, protein phosphatase 2A (PP2A), ubiquitin (UBQ), malic dehydrogenase (MDH), actin 1 (Actin), β-tubulin (TUB), and phenylalanine ammonia lyase (PAL) were selected. ΔCt, geNorm, NormFinder and BestKeeper were used to evaluate the stability of genes expression. The RefFinder program was utilized to comprehensively assess the optimal reference genes for C. alismatifolia bract.【Result】Results indicated that all the eight reference genes amplified a single peak, and the standard curve with R2 ≥ 0.98 and amplification efficiency value of 99.5%~125.0%. The PCR products were analyzed using 1% agarose gel electrophoresis and exhibited distinct and single bands, which suggested that the primers were highly specific. The ranking of results obtained from the four different algorithms varied. Specifically, MDH was identified as the most stable reference gene in the ΔCt, geNorm, and NormFinder methodologies analysis, whereas 18S rRNA was the most stable reference gene in the BestKeeper analysis. The comprehensive ranking of candidate reference genes stability was obtained using the RefFinder program, with the order from high to low being MDH > Actin > TUB > 18S rRNA > PP2A > GAPDH > UBQ > PAL. The most suitable reference gene for different cultivars of C. alismatifolia bract is MDH, followed by Actin and TUB, while PAL is the least stable and unsuitable as a reference gene for C. alismatifolia bract..【Conclusion】MDH can be used as a stable reference gene for different cultivars of C. alismatifolia bract, providing a reference for further analysis of the expression patterns of genes related to color synthesis in C. alismatifolia bracts.